The political economy of public expenditures in agriculture: Applications of concepts to Mozambique - Mogues, Tewodaj; do Rosario, D. (Wiley, 2016)
This paper undertakes an investigation of agricultural public investments in Mozambique, drawing on insights from qualitative field interviews conducted in Mozambique, secondary data analysis and examination of the existing empirical literature, and by situating these insights within a political economy conceptual framework. We explore the driving factors behind the amount and allocation of public funds to agriculture, and behind the differential attention that various types of public investments receive in the process of making decisions on resource allocation. Agricultural public investments are more likely to be made that have two key features: higher attributability to politicians and donors of the output of public spending, and a shorter lag time between expenditures incurred and outputs produced. Evidence on geographical targeting of agricultural public funds corresponds more closely with theories suggesting that resources are used to sway communities opposed to the ruling party, rather than to reward political supporters. Examination of the effect of actors' and organisations' incentives and constraints on resource allocation in agriculture points to the importance of not treating “government,” “the ruling party” and other institutions as monolithic bodies; the paper instead highlights how differentiated interests within seemingly coherent institutions drive what gets public expenditure attention in the agricultural sector.